2015
DOI: 10.18632/oncotarget.5857
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib enhances expression of effector molecules in anti-tumor CD8+ T lymphocytes by promoting Notch-nuclear factor-κB crosstalk

Abstract: The immunosuppressive tumor microenvironment usurps host antitumor immunity by multiple mechanisms including interference with the Notch system, which is important for various metazoan cell fate decisions and hematopoietic cell differentiation and function. We observed that treatment with the proteasome inhibitor bortezomib in mice bearing various solid tumors resulted in an upregulated expression of various Notch signaling components in lymphoid tissues, thereby increasing CD8+T-lymphocyte IFNγ secretion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 63 publications
2
39
0
Order By: Relevance
“…MDSCs blocked the induction of full-length and cleaved Notch in T-cells through nitric oxide-dependent pathways (14). Also, the impaired Notch activity found in T-cells from tumor-bearing hosts was rescued by the proteasome inhibitor bortezomib, suggesting the post-translational regulation of T-cell-Notch in tumors (34). Additional data showed that methylation of the Notch regulator, Numb, triggered Notch activity upon T-cell stimulation, indicating the epigenetic regulation of Notch signaling in T-cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs blocked the induction of full-length and cleaved Notch in T-cells through nitric oxide-dependent pathways (14). Also, the impaired Notch activity found in T-cells from tumor-bearing hosts was rescued by the proteasome inhibitor bortezomib, suggesting the post-translational regulation of T-cell-Notch in tumors (34). Additional data showed that methylation of the Notch regulator, Numb, triggered Notch activity upon T-cell stimulation, indicating the epigenetic regulation of Notch signaling in T-cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…232 Thounaojam and colleagues (from Meharry Medical College, Nashville, TN, USA) found that bortezomib suppresses the growth of various solid tumors by upregulating the expression of various components of the Notch signaling pathway in lymphoid tissues including CD8 C CTLs, resulting in increased cytotoxic functions. 219,233 Guillerey and collaborators (from QIMR Berghofer Medical Research Institute, Herston, Australia) observed that anti-myeloma immune response elicited by bortezomib or cyclophosphamide critically relies on CD226, which is crucial for the effector and cytotoxic functions of NK and CD8 C T cells. 234 Finally, Wong and collaborators (from National University of Singapore, Singapore) screened a library of chemotherapeutically active platinum derivatives and characterized a Pt(II) N-heterocyclic carbene complex as a putative inducer of ICD (pending in vivo validation), based on its capacity to trigger oxidative ER stress, CALR exposure, ATP secretion, and HMGB1 release.…”
Section: Recent Preclinical Developmentsmentioning
confidence: 99%
“…The presence of titanium particles in the peri-implant region can be an obstacle for bone regeneration. At the same time BTZ has also been shown to induce NF-κB pathways in immune cells in cancer immunotherapy when used for cancer combinatorial approach, suggesting that the effect of BTZ may be cell-specific 54 . Further research is needed if we are to make further clinical use.…”
Section: Discussionmentioning
confidence: 99%